Sistem Perbankan Islam di Malaysia: Sejarah Perkembangan, Prinsip dan Amalannya - Borhan, Joni Tamkin (Jurnal Usuluddin, 2001)
This article discusses the historical development of Islamic Banking System in Malaysia followed by the establishment of the interest-free banking schemes, the principles of profit and loss sharing and the operation of Malaysian Islamic banking system based on the Syari’ah Principles of Fiqh Muamalat.